Compliance evaluation of removable space maintainer or space regainer usage - Ramadhani, Revanti; Hidayat, Syarief; Primarti, Risti Saptarini (Padjadjaran Journal of Dentistry, 2012)
Premature loss could cause a problem with the tooth arrangement or the dental arch size. A space left by the primary tooth loss could cause migration of the adjacent teeth. As a result, space will be narrowed and undermined the eruption of the permanent teeth. The success of the space maintainer or space regainer usage due to the premature loss marked by space for the replacement of the permanent teeth. The purpose of this research was to evaluate the compliance of children in wearing a space maintainer or space regainer after insertion at Pedodontics Installation of Faculty of Dentistry Universitas Padjadjaran Dental Hospital, Bandung, Indonesia. The research method was descriptive survey technique. The sample consisted of 30 patients selected using the total sampling technique. Data were obtained with a questionnaire and statistically analyzed. The results showed that majority of the children uses the removable space maintainer or the space regainer daily was only about 23,3% overall. Most of the children only use the removable space maintainer or the space regainer for sometimes. The research concluded that the low rate of pedodontic patients compliance at Pedodontics Installation of Faculty of Dentistry Universitas Padjadjaran Dental Hospital in the usage of the removable space maintainer or the space regainer was usually caused by pain or discomfort. This fact was evidence of a low awareness of parents in preventing malocclusion to their children.